2019
DOI: 10.1002/asia.201901049
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Construction of C−Se And C−S Bonds via the Visible‐Light‐Mediated Multicomponent Cascade Reaction of Diselenides, Alkynes, and SO2

Abstract: A visible‐light mediated multicomponent cascade reaction of diselenides, alkynes, and sulfur dioxide was developed, in which multiple C−Se and C−S bonds were constructed, and unexpected β‐sulfonylvinylselane compounds were generated with high selectivity for E configuration. β‐Sulfonylvinylselane transformation into 1,4‐oxathiine‐4,4‐dioxide and sulfonylethyne derivates was then investigated. A plausible mechanism involving a selenium radical‐initiated cascade reaction and sulfur dioxide insertion was proposed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…All these advantages have meant that in the last seven years there has been a significant increase in the number of works reporting the use of photochemistry in the seleno-functionalization of several classes of organic substrates [ 70 ]. For example, the carbon-selenium bond formation in heteroarene-like indoles [ 71 , 72 ], imidazo[1,2 a ]pyridines [ 73 , 74 ], coumarines [ 75 ], benzothiazoles [ 76 ] and pyridines [ 77 ]; selenylation of naphthols [ 78 ], terminal alkenes [ 79 , 80 ] and alkynes [ 81 , 82 ] and sp 3 carbons [ 83 , 84 ]; and selenocyclization reactions have been reported [ 85 , 86 ]. In these protocols, in general, the substrate, the selenylating reagent and the photocatalyst are stimulated by visible light irradiation via single electron transfer (SET) reactions.…”
Section: Application Of Non-conventional Energy Sources In Organosele...mentioning
confidence: 99%
“…All these advantages have meant that in the last seven years there has been a significant increase in the number of works reporting the use of photochemistry in the seleno-functionalization of several classes of organic substrates [ 70 ]. For example, the carbon-selenium bond formation in heteroarene-like indoles [ 71 , 72 ], imidazo[1,2 a ]pyridines [ 73 , 74 ], coumarines [ 75 ], benzothiazoles [ 76 ] and pyridines [ 77 ]; selenylation of naphthols [ 78 ], terminal alkenes [ 79 , 80 ] and alkynes [ 81 , 82 ] and sp 3 carbons [ 83 , 84 ]; and selenocyclization reactions have been reported [ 85 , 86 ]. In these protocols, in general, the substrate, the selenylating reagent and the photocatalyst are stimulated by visible light irradiation via single electron transfer (SET) reactions.…”
Section: Application Of Non-conventional Energy Sources In Organosele...mentioning
confidence: 99%
“…The synthesis of β ‐(seleno)‐vinyl sulfones was also carried out photochemically by Chen and co‐workers using alkynes 105 , diphenyl diselenide 50 , DABCO ⋅ (SO 2 ) 2 and blue LEDs with high selectivity for the E stereoisomer (Scheme 29). [54] The proposed mechanism involves a domino reaction, which begins with photochemical homolytic Se−Se bond cleavage of the diphenyl diselenide 50 leading to the phenylselenyl radical 119 . The addition of this radical to the terminal carbon on the alkyne produces the vinyl radical 124 , which traps SO 2 to afford the sulfonyl radical intermediate.…”
Section: Selenylation Of Other Multiple Bondsmentioning
confidence: 99%
“…Sun et al, reported a radical-initiated seleno difluoromethylation of alkenes promoted by copper salt. [179] Ogawa's group developed multicomponent cascade reactions of diselenide 4, alkyne 311 with: (i) alkene, [180][181][182][183][184][185][186] (ii) benzoyl peroxide (BPO), [187] and (iii) (Ph 2 P) 2 , [188] (iv) multicomponent cascade reaction of diselenides, alkynes, and sulfur dioxide by using a visible-light in which multiple CÀ Se and CÀ S bonds were constructed, [189] (v) palladium-catalyzed YÀ Y (Y=S, Se) bond addition to alkynes under solvent-free conditions (Scheme 100). [190] The synthesis of bis-selenide alkenes 319 and trisselenide alkenes 320 from alkynyl carboxylic acids 318 and diselenides 4 is shown in Scheme 101.…”
Section: Synthesis Of Bis-and Tris-selenide Alkenementioning
confidence: 99%